2017
DOI: 10.1080/01490451.2017.1339144
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Keratinase and Other Hydrolytic Enzymes in Thermophilic Bacteria Isolated from Geothermal Areas in Patagonia Argentina

Abstract: Thermophilic aerobic bacteria were isolated from two geothermal areas in Neuqu en province using two different enrichment methods and a total of 30 isolates were obtained. From chicken feather enrichment cultures, strains affiliated to Bacillus cytotoxicus and Bacillus licheniformis were isolated and all of them demonstrated the capability to degrade completely chicken feather. A preliminary research on biotechnological enzymes' potential demonstrated that all the isolates displayed at least one of the extrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 57 publications
0
16
0
2
Order By: Relevance
“…Moreover, protease activities of Paenibacillus species were screened in this study. However, there are a few studies about protease of Paenibacillus isolated from thermophilic area [30][31][32][33]. Besides, there is no study about protease of Paenibacillus lactis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, protease activities of Paenibacillus species were screened in this study. However, there are a few studies about protease of Paenibacillus isolated from thermophilic area [30][31][32][33]. Besides, there is no study about protease of Paenibacillus lactis.…”
Section: Discussionmentioning
confidence: 99%
“…Production abilities of hydrolytic enzymes including keratinases, proteases, esterases, amylases, cellulases, inulinases, pectinases and xylanases from thermophilic isolates were investigated in study. 83% of screened isolates containing Paenibacillus dendritiformis was reported to have protease activity [32]. Panosyan investigated production abilities of hydrolytic enzymes from thermophilic bacilli including Paenibacillus genus.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of phylogenetic analysis, the strains 1S and 4S were closely related to type strain B. subtilis subsp. inaquosorum (CP013984) with 99.92 and 100% respectively 29,46 . The sequencing results revealed that the genus Bacillus was predominant rather than Geobacillus and Aeribacillus in sand dunes of Thar Desert.…”
Section: Journal Of Pure and Applied Microbiologymentioning
confidence: 99%
“…Patagonia in the southwest of Argentina presents two volcanic geothermal areas-Copahue and Domuyo. The Copahue geothermal area, predominantly acidic, has been extensively studied as for its prokaryotic biodiversity [2][3][4] and the biotechnological applications of some of their species [5][6][7]. On the other hand, the Domuyo geothermal area remains almost unexplored in both aspects.…”
Section: Introductionmentioning
confidence: 99%